PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, KETERLIBATAN PERSONAL DAN PARTISIPASI MANAJEMEN TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADA ASSALAAM HYPERMARKET - Aprilia Eka Putri; Bambang Widarno (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
This research aims to determine the effect of human resource competence, personal involvement, and management participation on the effectiveness of accounting information systems. The research object is conducted at Assalaam Hypermarket, and the type of data used is quantitative data. The sample used comprises 64 respondents. The sampling technique is carried out using the Purposive Sampling method.. Data analysis techniques include descriptive tests, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis tests, hypothesis tests, and model accuracy tests. The results of this study indicate that Human Resource Competence has a negative and insignificant effect, Personal Involvement, Management Participation has a positive and significant effect on the Effectiveness of Accounting Information Systems.